2016
DOI: 10.1140/epjc/s10052-016-4357-5
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Landau levels in the rotating cosmic string spacetime

Abstract: In the spacetime induced by a rotating cosmic string we compute the energy levels of a massive spinless particle coupled covariantly to a homogeneous magnetic field parallel to the string. Afterwards, we consider the addition of a scalar potential with a Coulomb-type and a linear confining term and completely solve the Klein-Gordon equations for each configuration. Finally, assuming rigid-wall boundary conditions, we find the Landau levels when the linear defect is itself magnetized. Remarkably, our analysis r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 41 publications
(62 reference statements)
1
66
0
2
Order By: Relevance
“…These energy levels have already been considered previously by the authors in Refs. [25][26][27][28][29], which shows the consistency of our results.…”
Section: A Schrödinger Equationsupporting
confidence: 86%
See 2 more Smart Citations
“…These energy levels have already been considered previously by the authors in Refs. [25][26][27][28][29], which shows the consistency of our results.…”
Section: A Schrödinger Equationsupporting
confidence: 86%
“…The study of the Landau levels in the presence of a standard cosmic string (or a disclination in condensed matter systems) was already performed in [25][26][27][28][29], and we will follow the same line of investigation. In this case, the Hamiltonian corresponding to a charged particle in the presence of a gauge field in a curved background given generically by a metric g ij is written asĤ…”
Section: Landau Levels In the Rainbow Gravity Cosmic String Spacmentioning
confidence: 99%
See 1 more Smart Citation
“…The last point we would like to comment on here is that it would be natural now to attempt to apply the same techniques used above to the case of a rotating cylinder. Unfortunately, however, to deal with such a case one has to use the so-called Lewis spacetime [35], which is even more complicated than the metric (II.2). Given that the Lewis spacetime reduces in the limit of zero radius of the cylinder to that of a rotating cosmic string (see, e.g., Ref.…”
Section: B Using the Harmonic Oscillator Approximationmentioning
confidence: 99%
“…In Ref. [23], relativistic Landau levels in the rotating cosmic string space-time with the Cornell potential, is considered. It was shown that the Landau levels of the spinning cosmic string remain the same even when the internal magnetic flux vanishes.…”
Section: Introductionmentioning
confidence: 99%